Bibliometric Analysis of Zakat Development in Indonesia During the Covid-19 Pandemic - Ismail Ismail; Misrah Misrah; Andri Soemitra (ITB AAS INDONESIA Surakarta, 2022)
Zakat is one of the financial instruments that can be used by people in Indonesia in dealing with problems of helping, during the current difficult times, COVID-19 has hit for approximately two years, many workers and business actors who have zakat, both consumptive and productive, the people affected by this disaster have become very helped. This research is a literature study by explaining the extent of zakat research during the COVID-19 pandemic by obtaining the results of 55 selected journals from 843 published journals on Google Schoolar using the Publish or Perish application. The next result of this study is how to play zakat as an alternative to Islamic finance in alleviating poverty.